2014
DOI: 10.1038/srep04042
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Role of Cytosolic Phospholipase A2α in Dioxin-induced Neonatal Hydronephrosis in Mice

Abstract: Hydronephrosis is a common disease characterized by dilation of the renal pelvis and calices, resulting in loss of kidney function in the most severe cases. 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) induces nonobstructive hydronephrosis in mouse neonates through upregulation of prostaglandin E2 (PGE2) synthesis pathway consisting of cyclooxygenase-2 (COX-2) and microsomal prostaglandin E synthase-1 (mPGES-1) by a yet unknown mechanism. We here studied possible involvement of cytosolic phospholipase A2α (cPLA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Elevated cellular Ca 2+ levels activate Ca 2+ /calmodulin‐dependent kinases (CaMK), which, in turn, may modulate nuclear translocation of the AHR (red arrow in Figure ) (Monteiro et al., ; Gilot et al., ). The in vivo relevance of these findings has been shown for body weight loss and developmental hydronephrosis in mice (Yoshioka et al., ; Fujisawa et al., ). Other examples of alternative pathways include the AHR‐mediated repressed expression of acute‐phase proteins such as serum amyloid A 3 in mouse hepatocytes (9. in Figure ) (Patel et al., ) and functioning of the AHR as a nuclear E3 ubiquitin ligase.…”
Section: Assessmentmentioning
confidence: 72%
“…Elevated cellular Ca 2+ levels activate Ca 2+ /calmodulin‐dependent kinases (CaMK), which, in turn, may modulate nuclear translocation of the AHR (red arrow in Figure ) (Monteiro et al., ; Gilot et al., ). The in vivo relevance of these findings has been shown for body weight loss and developmental hydronephrosis in mice (Yoshioka et al., ; Fujisawa et al., ). Other examples of alternative pathways include the AHR‐mediated repressed expression of acute‐phase proteins such as serum amyloid A 3 in mouse hepatocytes (9. in Figure ) (Patel et al., ) and functioning of the AHR as a nuclear E3 ubiquitin ligase.…”
Section: Assessmentmentioning
confidence: 72%
“…Abnormalities in the nuclear envelope, nuclear pore, and synapses were observed. The authors speculated that this could be due to the role of shown that cPLA 2 ␣ plays a role in mediating the onset of nonobstructive neonatal hydronephrosis, induced in mice by treatment with 2,3,7,8-tetrachlorodibenzo-p-dioxin, which increases expression of cPLA 2 ␣ in the kidneys ( 163 ). Results showed that cPLA 2 ␣ KO neonates have reduced incidence and severity of hydronephrosis that correlates with reduced expression of COX-2, mPGES-1, and lower urinary PGE 2 compared with 2,3,7,8-tetrachlorodibenzo-p-dioxintreated WT pups.…”
Section: Reproductionmentioning
confidence: 99%
“…The role of AQP2 in the onset of hydronephrosis is not clear because there are some inconsistent observations on the abundance of AQP2 and its localization in the different experiments, such as pharmacological inhibition of V2R (5), nonsense mutation of V2R (58), and our present ( Fig. 4) and previous studies (2,35,55). Studies on short-term regulation and long-term adaptation of apical-trafficking, endocytosis, and expression of AQP2 may elucidate the underlying mechanism.…”
Section: F757mentioning
confidence: 52%
“…Endogenous factors downstream of AhR are believed to modulate a variety of toxic effects, but the mechanism of pathogenesis is not clear (56). Among these, genes encoding enzymes for the production of prostaglandins are responsible for the onset of TCDD-induced neonatal hydronephrosis in mice (35,53,55). AhR-dependent upregulation of cyclooxygenase-2 (COX-2) (10, 35) was shown to play a critical role in the onset of this disease, and the role this was confirmed by the abrogation of TCDD-induced hydronephrosis by treatment with a COX-2-selective inhibitor (35).…”
mentioning
confidence: 99%